Implementation of Data Governance on the Open Government Data Management Platform to Improve Data Quality - Khairul Habibie; Suhardi Suhardi; Wardani Muhamad (IJAIT (International Journal of Applied Information Technology), 2023)
Currently, realizing good governance related to data disclosure in government agencies is an initiative as a manifestation of open government data. However, there are still problems with the quality of published data. As a solution, organizations need to establish policies, strategies, and initiatives for data management activities This paper proposes adding data management activities to the platform to enhance the quality of published data. As for the value of the quality of the data tested using the XYZ district budget, there is an increase in the uniqueness quality dimension from valid DQI 98.7203 to 100; the conformity quality dimension has also increased from 94.7368 to 100; the accuracy quality dimension also increased significantly from 0 to 100; integrity quality dimension increased from 66.6667 to 100. As a concern, the validity of the data is by manual checking after deleting data duplication.